PENGARUH GREEN CAMPAIGN #BRINGBACKOURBOTTLE THE BODY SHOP TERHADAP SIKAP RAMAH LINGKUNGAN (Survei Pada Followers Instagram The Body Shop Indonesia @thebodyshopindo) - Iman Sunarya, (2022)
The development of the beauty industry is not realized that the spread of plastic waste in the form of packaging is also increasing. The community feels the need to change behavior in a direction that is more environmentally friendly. This study reveals the effect of the green campaign carried out by The Body Shop on environmentally friendly attitudes carried out by the community as consumers. The green campaign carried out by The Body Shop is not only to promote products to the public, but the body shop also invites the public to participate in environmental conservation starting from small things, namely choosing environmentally friendly products. This research process uses quantitative methods with surveys through questionnaires to 100 followers of @thebodyshopindo. The results of this study indicate that there is a large influence from the green campaign carried out by The Body Shop on environmentally friendly attitudes carried out by the community with an influence percentage of 84.6%. People are influenced to start being friendly to the environment around them from the smallest things.